2019
DOI: 10.3390/coatings9120815
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Ni–W/Cr2O3 Nanocomposite Coatings Using Electrochemical Deposition Technique

Abstract: Ni–W/Cr2O3 nanocomposite coatings were synthesized from aqueous sulphate-citrate electrolyte containing Cr2O3 nanoparticles on a steel surface using conventional electrodeposition technique. This study was aimed at investigating the influence of Cr2O3 nanoparticle content on the microstructure, corrosion resistance, and mechanical properties of electrodeposited Ni–W/Cr2O3 nanocomposite coatings. Ni–W binary alloy coatings were deposited and optimized before addition of the nanoparticles to produce high-quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 48 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…It appears that the increase in SiC nanoparticles further induced the formation of nucleation sites. Other researchers in their studies also observed the nodular morphology[31]. It can be seen that from 3-6 g.L -1 of SiC, the morphologies of Ni-W-SiC coatings fabricated on the polished samples had no micro-crack and defects but with 12 g.L -1 of SiC the coating morphology contained some defects.…”
mentioning
confidence: 67%
“…It appears that the increase in SiC nanoparticles further induced the formation of nucleation sites. Other researchers in their studies also observed the nodular morphology[31]. It can be seen that from 3-6 g.L -1 of SiC, the morphologies of Ni-W-SiC coatings fabricated on the polished samples had no micro-crack and defects but with 12 g.L -1 of SiC the coating morphology contained some defects.…”
mentioning
confidence: 67%
“…The average crystallite size of coatings in electrodeposits (Zn-Ni, Zn-Ni-WC) was subjected to XRD analysis (Philips PW 3710 XRD, Amelo, The Netherland) with copper Kα radiation (set at 30 mA and 40 kV)). Methods such as Williamson-Hall plot, Le Bail, Warren-Averbach, and Scherrer's models can be applied to determine the crystal size of the coating deposits [64][65][66]. In the present work, the Scherrer equation (Equation ( 1)) was applied to estimate the average crystallite size of electrodeposits based on the XRD data patterns (i.e., peak width at mean height) [51,63,64].…”
Section: Microstructural Characterizationmentioning
confidence: 99%
“…This comprises of degreasing using electro-hydrostatic fluid, then removal of oxide layer by passing the substrates through a strong activating solution, and finally removal of carbon-black by passing the substrates through a weak activating solution [49]. A similar pre-treatment process has been used in other coatings like Ni-W nanocomposite coatings with good adhesion translating to superb wear resistance achieved [146]. This pre-treatment process provides interesting possibilities for future use in Ni-Co alloys and nanocomposites.…”
Section: Future Scope and Recommendationsmentioning
confidence: 99%